An update on emerging drugs for fibromyalgia treatment. (2nd October 2017) - Atzeni, Fabiola; Gerardi, Maria Chiara; Masala, Ignazio Francesco; Alciati, Alessandra; Batticciotto, Alberto; Sarzi-Puttini, Piercarlo
ABSTRACT: Introduction : Fibromyalgia (FM) is a chronic disorder whose symptoms of pain, fatigue, sleep disturbances and depression have a devastating effect on patients' lives as it limits their ability to engage in everyday working and social activities, and make it difficult to maintain normal relationships with family, friends and employers. None of the currently available drugs are fully effective against the whole spectrum of symptoms. The aim of this narrative review is to summarise the data relating to the new therapeutic options that have become available over the last few years. Areas covered : Increasing efforts by the pharmaceutical industry have led to the introduction of new investigational drugs and new formulations of older drugs, and studies have been carried out in order to investigate the possibility of using drugs that are currently used for other diseases. Expert opinion : Slight improvements in the health of FM patients treated with drugs targeting a range of molecular mechanisms have been observed, but there is still no single drug that is capable of offering substantial efficacy against all of the characteristic symptoms of FM. The identification of new and improved therapies for FM requires consideration of the heterogeneity of the condition, which suggests the existence of different patient subgroups, a relationship between central and peripheral aspects of the pathophysiology, and the need for combined treatment with drugs targeting multiple molecular mechanisms.